Are Groves-Ledyard Equilibria Attainable? - Muench, Thomas; Walker, Mark (Review of Economic Studies, 1983)
Thomas Muench, Mark Walker; Are Groves-Ledyard Equilibria Attainable?, The Review of Economic Studies, Volume 50, Issue 2, 1 April 1983, Pages 393–396, htt